Otoritas Dinas Lingkungan Hidup Terhadap Pengawasan Pembuangan Limbah Cair Pabrik Kelapa Sawit Kabupaten Kotawaringin Timur Berdasarkan Hukum Normatif Dan Syariah - Tohirokhi Minallah; Surya Sukti; Muhammad Lutfi Setiarno (Kamaya: Jurnal Ilmu Agama, 2025)
The management of palm oil mill effluent (POME) in East Kotawaringin Regency has become a crucial issue due to its potential to cause water pollution and ecosystem degradation. Discharging effluent that exceeds quality standards not only violates statutory regulations but also contravenes Islamic principles prohibiting environmental damage (fasad fil-ardh). This study aims to analyze the authority of the Environmental Agency (DLH) in supervising the disposal of palm oil mill effluent based on normative law and to examine its alignment with environmental law principles from the perspective of Sharia. The research employed a normative juridical method with a qualitative approach, utilizing legal analysis of statutory regulations, Islamic environmental jurisprudence literature, and field data obtained through interviews and document analysis. The results indicate that normatively, DLH holds full authority to conduct routine inspections, collect effluent samples, enforce administrative sanctions, and provide guidance to companies. However, the implementation of supervision faces challenges such as limited human resources, insufficient budget, and low industry awareness. From the Sharia perspective, such supervision aligns with the human responsibility as khalifah (steward) on earth to preserve the environment and prevent damage. In conclusion, the effectiveness of effluent supervision requires strengthening institutional capacity, increasing legal awareness based on Sharia values, and fostering active community collaboration to achieve a clean, healthy, and sustainable environment in accordance with both positive law and Sharia principles.